Late diagnosis of complete androgen insensitivity syndrome and transmission/carriers of the condition in a family with mutation c.2495G> T p.(Arg832Leu) in exon 7 of the androgen receptor gene: genetic, clinical and ethical aspects - Pomahacova, Renata; Zamboryova, Jana; Paterova, Petra; Krepelova, Anna; Subrt, Ivan; Jaklova, Radka; Vohradska, Petra; Hrdonkova, Eliska; Sykora, Josef (Biomedical papers, 2019)
Background: The complete androgen insensitivity syndrome (CAIS) is a rare genetic disorder causing insensitivity to androgens in a person with female phenotype and 46,XY karyotype due to a mutation in the androgen receptor gene located on chromosome X. These children are born with female external genitalia, and females are transmitters. Case Report: We illustrate an unexpected diagnosis of CAIS in two siblings during examination for short stature, and describe transmission/carriers in the family along with ethical aspects. Conclusion: A genetic examination could have earlier revealed the transmission of c.2495G>Tp.(Arg832Leu) mutation in exon 7. Our experience highlights the possibility of prenatal testing for the management of pregnancy in a family with a history of CAIS. The implications of prenatal testing in relation to CAIS with clearer explication of ethical and clinical issues warrant further investigation.
Keywords: androgen insensitivity syndrome; chromosome X; transmission of the disease; prenatal testing; ethics